Procedural Legitimacy in Electoral Dispute Adjudication: Assessing the Role of Constitutional Courts in Safeguarding Democratic Integrity - Muhammad Asmawi (Jurnal Hukum Replik, 2026)
Procedural legitimacy in the resolution of electoral disputes constitutes a critical element in maintaining democratic integrity. This study examines the role of the Constitutional Court in ensuring compliance with legal norms, protecting citizens’ constitutional rights, and fostering public acceptance of electoral outcomes. Employing a qualitative method with a normative juridical approach, this research analyzes constitutional provisions, electoral laws, and the adjudicative practices of the Constitutional Court. The findings indicate that the Court has consistently applied principles of transparency, impartiality, participation, and accountability throughout its proceedings, thereby upholding normative legitimacy. However, a gap persists between normative and empirical legitimacy, particularly in relation to public perceptions of the complexity of judicial decisions and the potential for political bias. This study underscores that the effectiveness of procedural legitimacy is determined not only by legal compliance but also by the Court’s capacity to bridge public perception. Such capacity is essential to sustaining democratic integrity, ensuring the credibility of electoral outcomes, and preserving political stability.Keywords:Procedural legitimacy, Constitutional Court, electoral disputes, democratic integrity, constitutional law